Ekspresi Caspase-3 sebagai Petanda Apoptosis Makrofag Lesi Kulit Penderita Kusta Tipe Pausibasiler dan Multibasiler - Anggun P Yuniaswan; Santoso Basuki; Delya Widasmara (Pustaka Kesehatan, 2019)
Macrophage and Schwann cells are target cell on leprosy disease, where apoptotic is assumed as one of elimination mechanism of macrophage previously infected by M.leprae. Several study showed various result in apoptotic on leprosy disease. Apoptotic level can be evaluated by observing caspase-3 activity, an executioner caspase on cell death. This study is aimed to observe the relationship of caspase-3 expression with paucibacillary and multibacillary types of leprosy. We used observational analytic and cross sectional study with consecutive sampling method. The subject was leprosy patient which had been diagnosed on dermatovenereology division outpatient clinic Saiful Anwar Hospital, and fullfilled the inclusion-exclusion criteria. Total subject was 19 persons (11 multibacillary and 8 paucibacillary). Sampling was taken with punch biopsy on skin lession, followed by immunohistochemical staining with caspase-3 antibody, and caspase-3 expression was measured by ImmunoRatio method. Comparation test revealed significant difference (p<0.05%) between caspase-3 expression mean on paucibacillary patient (84.46%) compared to multibacillary patient (65.39%). Pearson correlation test revealed caspase-3 expression tend to be higher in paucibacillary patient than multibacillary (coefficient correlation -0.759). In conclusion, there is a significance relationship between caspase-3 expression with leprosy type.